Evaluating the effectiveness of digital health interventions on reducing hospital readmissions in heart failure patients - Saharan, Priyanka; Srinivasa Rao, Varri (Journal of Neonatal Surgery, 2025)
Heart failure (HF) remains one of the leading causes of hospitalization and readmissions, posing a significant burden on healthcare systems. Digital health interventions (DHIs), which utilize mobile applications, telemonitoring, and other digital tools to track and manage patient health, have emerged as promising strategies for reducing hospital readmissions in heart failure patients. This study aims to evaluate the effectiveness of DHIs in reducing the frequency of hospital readmissions among individuals with heart failure. A cohort of heart failure patients was randomized into two groups: one receiving standard care and the other receiving a digital health intervention consisting of remote monitoring, personalized feedback, and educational content delivered through a mobile app. Data was collected on readmission rates, hospital stays, clinical outcomes, and patient engagement with the digital platform over a 12-month period. The study found that the group receiving the digital health intervention experienced a 25% reduction in readmission rates compared to the control group. Furthermore, patients in the intervention group showed improved self-management behaviors, better adherence to prescribed treatment regimens, and improved quality of life. These findings suggest that digital health interventions can play a significant role in reducing hospital readmissions for heart failure patients, improving clinical outcomes, and lowering healthcare costs.